1995
DOI: 10.1039/ft9959102907
|View full text |Cite
|
Sign up to set email alerts
|

Acidic and basic properties of titania–alumina mixed oxides; active sites for propan-2-ol dehydration

Abstract: Ti0,-AI,O, mixed oxides have been prepared by cohydrolysis of Ti4' and A13+ isopropoxides, Textural and acid-base properties were investigated using nitrogen physisorption, adsorption of probe molecules followed by FTIR spectroscopy, and test-reactions. Catalysts were found to exhibit high surface areas and pore volumes. Results obtained from adsorbed CO, probe molecules and COS hydrolysis activity agreed well and showed that the hydroxy basicity of mixed oxides was lower than that of t h e two oxide component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 39 publications
(1 reference statement)
2
20
0
Order By: Relevance
“…Similar results were also reported by other researchers [5][6][7][8]. 10 Lithium-Based Lean-Burn NO x Trap Catalyst 237…”
Section: No X Storage Behaviorssupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were also reported by other researchers [5][6][7][8]. 10 Lithium-Based Lean-Burn NO x Trap Catalyst 237…”
Section: No X Storage Behaviorssupporting
confidence: 93%
“…Matsumoto et al [9] found that the decomposition temperature of sulfates on TiO 2 support is lower than that on Al 2 O 3 support under reducing conditions. Lahousse et al [10] studied the acidic and basic properties of TiO 2 -Al 2 O 3 mixed oxides and its activity for propanediol dehydration. Their results show that TiO 2 -Al 2 O 3 mixed oxides exhibit better thermal stability and larger acidity than the two single oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Such correlation was already reported between the activity for carbon oxysulfide hydrolysis of various mixed oxides (TiO 2 -Al 2 O 3 , TiO 2 -ZrO 2 and ZrO 2 -Al 2 O 3 ) and the intensity of the band at 1225 cm -1 . 48,49 As observed in Fig. 4 attributed to the presence of carbonates species produced by reaction with CO 2 .…”
Section: -50mentioning
confidence: 84%
“…For all other samples, several bands appeared between 1100 -1900 cm -1 , showing that some basic sites remained available to adsorb CO 2 and to form carbonate and bicarbonate species. [48][49][50] The decrease of the fluorine content is linked to an increase of several bands, including notably those located at 1358 and 1460 cm -1…”
mentioning
confidence: 99%
“…The scheme describes four simultaneous processes of isopropyl chloride, propylene, n-propyl chloride and diisopropyl ether formation from isopropanol. In summary, the entire process can be presented as a combination of parallel reaction carried out on γ-alumina surface according to E1 and Snull1 mechanisms [52][53][54][55][56][57][58][59][60][61][62]. First, step 1 depicts the protonation stage -interaction of isopropanol with γ-alumina acid sites via OH-group [55,61] (which can also result in partial transformation of Lewis acid sites into Brønsted sites [62]), followed by dehydration step by E1 mechanism towards secondary propyl carbocation I (step 2).…”
Section: Reaction Mechanismmentioning
confidence: 99%